LEFT ADRENAL TUBERCULOSIS MIMICKING PHAEOCHROMOCYTOMA POSSIBLY DUE TO RIFAMPICIN INTERFERENCE IN URINE METANEPHRINES - Azmi, Ahmad Mustakim Nor; Azman, Siti Sanaa Wan; Ali, Masliza Hanuni Mohd; Li, Cheng Mao; Mohamed, Hussain; Muda, Nor Hisham; Ali, Nurul Atiah Mohd (Journal of the ASEAN Federation of Endocrine Societies, 2025)
INTRODUCTION/BACKGROUND Phaeochromocytoma classically presents with uncontrolled hypertension and paroxysms of headache, diaphoresis and palpitations. The measurement of 24-hour urinary metanephrines is one of the standard first-line tests for detecting phaeochromocytoma. False elevation results may be brought about by various factors such as urine volume, medication interference and certain foods. CASE We report a case of a 67-year-old male with Hepatitis B and smear-positive pulmonary tuberculosis on maintenance treatment with rifampicin and isoniazid, who was referred for left adrenal incidentaloma from CT of the hepatobiliary system. He denied any paroxysmal symptomatology of phaeochromocytoma and was normotensive. 24-hour urinary metanephrines revealed significantly elevated normetanephrine (14 times the upper limit of normal [30.15 µmol/day]), with normal metanephrine and 3-methoxytyramine levels. The adrenal CT demonstrated a left adrenal mass measuring 2.7 x 1.4 x 2.6 cm, 32 Hounsfield units (HU), with absolute and relative washout of 62.8% and 19.6%, respectively, indicating an indeterminate adrenal mass. The patient was diagnosed with left phaeochromocytoma and underwent laparoscopic left adrenalectomy with Phenoxybenzamine cover. However, the histopathological findings revealed multiple granuloma formation, with special stains negative for acid-fast bacilli, suggestive of chronic changes of right adrenal tuberculosis (non-active) and no features of phaeochromocytoma. Thoracic and abdominopelvic CT scans showed no evidence to suggest paraganglioma, which might contribute to elevated normetanephrine levels. A post-operative repeat 24-hour urine metanephrine came back normal. This repeated sample was taken after the patient completed tuberculosis treatment (including rifampicin). Some reports recognised rifampicin interference with urinary metanephrine measurement as it is eluted with normetanephrine, causing significantly elevated levels. These findings correlate with this patient as urine normetanephrine returned to normal once he was off rifampicin. CONCLUSION Histopathological findings of the left adrenal mass were suggestive of post-adrenal tuberculosis rather than phaeochromocytoma. Rifampicin was found to be an interferent in urine metanephrines measurement, which led to falsely elevated normetanephrine levels with no catecholaminergic signs or symptoms.